Wassilni - Adam Abdalhafez; Amro Sous (My University, 2025)
The Wassilni project aims to enhance public transportation by providing a more efficient and user-friendly booking system. With increasing urban congestion and demand for reliable transport, Wassilni simplifies the process of booking public buses, reducing waiting times and offering real-time tracking. The system integrates modern technologies, including GPS, AI, and mobile applications, to improve the commuting experience. Key features of the project include a React Native mobile application for riders to register, select destinations, and book buses based on proximity and route availability. The driver’s route and pick-up points are dynamically generated, allowing real-time tracking of the vehicle. The system also incorporates checkpoints, which serve as predefined stops along the route. If a checkpoint is closed, the system suggests alternative routes to ensure seamless travel. Additionally, an AI-powered service updates checkpoint statuses based on driver communication, improving route planning and reducing delays. To further enhance the user experience, the system includes a waiting queue feature that notifies riders when no buses are currently available, helping them manage expectations. A driver rating system allows passengers to provide feedback, promoting service quality and accountability. The admin web dashboard enables administrators to manage drivers, routes, and monitor performance. The back-end is deployed on AWS ECS with MongoDB for efficient data handling, particularly for geospatial indexing to locate nearby vehicles and checkpoints. The system leverages the Google Maps API for routing and estimated arrival times. Unlike private ride-hailing services such as Uber or Careem, Wassilni focuses on optimizing public transportation, making it an innovative solution for improving daily commutes.